THE EFFECT OF PROBLEM BASED LEARNING (PBL) MODEL BASED ON AUDIO VISUAL MEDIA TO CREATIVE THINKING SKILLS OF STUDENTS - Ari Nofida; Syaiful Arif (Science Education, Institut Agama Islam Negeri Ponorogo, 2020)
This research aims to study the feasibility of learning models, student activities, and the presence or absence of problem-based learning models on the creative thinking skills of grade VII students at SMP Negeri 1 Mlarak. This research is a quasi-experimental study with a nonequivalent control group design. This study uses PBL learning models assisted by audio visual media for the experimental class and conventional models for the control class. The instrument used was a written test consisting of descriptions, while the statistical analysis used the t test (independent sample test) and one tail test.